THE PSYCHOANALYTICAL STUDY ON THE CHARACTERISTICS AND CAUSES OF ADOLESCENT DEVIANT BEHAVIOR FOUND IN DIVERGENT NOVEL BY VERONICA ROTH - Nurhasanah Putri Wiyani; Surya Sili; Nita Maya Valiantien (Fakultas Ilmu Budaya Universitas Mulawarman, 2017)
Abstract This research investigates how the major character described to get causes of Beatrice's deviant behaviors in Veronica Roth’s Divergent Novel. This research used three different theories to answer two research questions. First, used the personality theory by Sigmund Freud and used the four ds of abnormality theory by Ronald J.Comer to define the deviant behavior of the main character, Beatrice Prior. This research also used behavior disorder theory by Harry Gottesfeld to analyzed the causes of deviant behavior which is performed by the main character. The data sources are literary data. The method of data collection of the research is library research. The technique of data analysis is descriptive qualitative method. The researcher served the data in dialogues, and narratives by Beatrice. Based on the analysis, the researcher draws two conclusions: First, this research shows that the failure to control personality can make a person being deviant. It is reflected in the major character’s personality when she wants to leave her faction. The second, this research shows that there are four causes of Beatrice deviant behavior in six causes of behavior disorder, they are the physical, biological factors; the family; and the self-concept, and natural support systems. Key words : psychoanalytical study, deviant behavior, Divergent novel. Abstrak Penelitian ini menyelidiki bagaimana karakter utama dijelaskan untuk mengetahui penyebab perilaku menyimpang Beatrice di novel Divergent karya Veronica Roth. Penelitian ini menggunakan tiga teori yang berbeda untuk menjawab dua pertanyaan penelitian. Pertama, menggunakan teori personality oleh Sigmund Freud dan menggunakan teori the four Ds of Abnormality oleh Ronald J.Comer untuk menentukan perilaku menyimpang dari karakter utama, Beatrice Prior. Penelitian ini juga menggunakan teori behavior disorder oleh Harry Gottesfeld untuk menganalisis penyebab perilaku menyimpang yang dilakukan oleh karakter utama. Sumber data adalah data sastra. Metode pengumpulan data dari penelitian ini adalah studi pustaka. Teknik analisis data adalah metode deskriptif kualitatif. Peneliti menyajikan data dalam dialog, dan narasi oleh Beatrice. Berdasarkan hasil analisis, peneliti menarik dua kesimpulan: Pertama, penelitian ini menunjukkan bahwa kegagalan untuk mengontrol kepribadian dapat membuat seseorang menjadi menyimpang. Hal ini tercermin dalam kepribadian karakter utama ketika ia ingin meninggalkan faksi nya. Yang kedua, penelitian ini menunjukkan bahwa ada empat penyebab perilaku menyimpang Beatrice dalam enam penyebab gangguan perilaku, yaitu fisik, faktor biologis; keluarga; konsep diri, dan sistem pendukung alami. Kata kunci: penelitian psikoanalitik, perilaku menyimpang, novel Divergent